Instant Emotional Healing : Acupressure for the Emotions - Lambrou, Peter and Pratt, George (London Rider Books, 2000)
Shows you how to give yourself instant relief from negative emotions. Drawing on a combination of the meridian systems of Eastern acupuncture and Western cognitive ideas, the author offers step-by-step instructions on how to use key pressure points on your body, breathing techniques and focused thought to overcome negative feelings.
Include Glossary, Reference, Bibliography and Index
Keywords: Acupressure -- Mental health -- Mind and body therapies -- Self-management (Psychology)